Penggunaan Media Gambar dalam Proses Pembelajaran dapat Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Bayudi, Anton (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
As an effort to improve student learning outcomes in the learning process, one of them is by using learning media. Image is one of the learning media that can be used in learning. Picture media is a medium that is often used by teachers in delivering subject matter. So the image media is the media used to visualize or distribute messages from the source to the recipient (student). By using image media, students can understand the material presented by the teacher and are able to improve student learning outcomes. Learning outcomes are when someone has learned there will be a change in behavior in that person.